P53 Protein in Serum and Urine Samples of Patients with Bladder Transitional Cell Carcinoma and Its Overexpression in Tumoral Tissue - Darabi, Mohammadreza; Tayebi Meibodi, Nasser; Mahdavi, Reza; Arab, Davood (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the levels of p53 protein in serum and urine samples of patients with bladder transitional cell carcinoma (TCC) and their relation with the overexpression of p53 in the tumoral tissue. Materials and Methods: A total of 39 patients with bladder TCC were evaluated for p53 protein in their serum and urine samples and the overexpression of this marker in their tumoral tissue. Results: Of 39 patients with bladder TCC, 29 (74.4%) had tissue specimens positive for p53 protein overexpression, 20 (51.3%) had p53 protein in their serum samples, and 27 (69.2%) had this protein in their urine samples. A positive immunohistochemical finding was more common in higher grades of the bladder tumor (P = .03), but not in higher stages (P = .07). Eighteen of 20 patients (90%) with a positive serum for p53 showed protein overexpression in the tumoral tissue of the bladder (P = .03). Of 27 patients with a positive urine sample, 25 (92.6%) had p53 overexpression in their bladder tissue, and of the remainder 12 patients with a negative p53 protein in their urine samples, 8 (66.7%) had no evidence of p53 protein overexpression in their tumoral tissue (P < .001). The grade and stage of tumor had no correlation with serum or urinary p53. Conclusion: According to our findings, a positive serum or urine sample for p53 protein is highly associated with the overexpression of p53 protein in the tumoral tissue of patients with bladder TCC.